STUDI MORFOMETRI DAN TINGKAT HERBIVORI DAUN MANGROVE DI SEGARA ANAKAN CILACAP - Erma Septyaningsih; Erwin Riyanto Ardli; Ani Widyastuti (Scripta Biologica, 2014)
Mangrove communities are part of the natural coastal ecosystems that have a vital role, such as the greatest source of organic material for the surrounding aquatic environment. A variety of ecological phenomenon often happens recently, either directly or indirectly affects the change of mangrove vegetations. Leaf is one of the plant organs that change shape according to the condition of the mangroves and the aquatic environment where the plant lives. The common changes of the leaves are the symmetry (morphometry), the size, and the shape. Mangrove leaves are also subjected to herbivory (predation), that will result in reduced leaf area of the photosynthesis and lowered the production of organic matter to the surrounding waters. This research aimed to determine the morphometric variation and herbivory rates of mangrove leaves at Segara Anakan Cilacap. Mangrove samples were Aegiceras corniculatum, Avicennia marina, Ceriops tagal, Rhizophora apiculata, and Sonneratia caseolaris. The study used survey method with stratified random sampling technique. The results showed morphometric variations of the five species were three variations, while the average herbivory rate from highest to lowest were: Avicennia marina (7.46%), Sonneratia caseolaris (6.91%), Rhizophora apiculata (4.08%), Aegiceras corniculatum (3.42%) and Ceriops tagal (3.00%). The difference of age and species of leves affected the herbivory level.